Enhancing Students’ Writing Skills through the Implementation of the Seven Nucleus Approach in Teaching Tenses - Ahmed Sardi; Kalsum Kalsum; Wahyuddin Rauf; Suwardi Hasyim (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2023)
This study sought to determine whether teaching tenses using grammar exercises will enhance the student's writing skills in terms of language use, content, and structure. The seven-nucleus approach is being used at Cambridge English College (CEC) Makassar. This approach is a way to memorize tenses using seven certain verbs in English which are present, past, perfect, future, modal, and continues verbs. The current study employed a pre-experimental design with a single group for the pre and post-tests. The sample only included one class of 10 pupils, chosen using the technique of cluster sampling. The results demonstrated that the student’s writing ability had improved. It was three indicators of progress: language use had improved by 22.96%; content had improved by 12.3%; and organization had improved by 22.83%. The overall improvement was 19.48%. When compared to the pretest before the treatment, the student's writing competence was 1950 on the posttest, and the value of the t-test (7.440) was higher than the t-table (2.262). The research concluded that the use of seven Nucleus was beneficial in improving students' skills of writing in terms of the language writing content, and organization at Cambridge English College (CEC) Makassar based on its findings and discussion.